2006
DOI: 10.1002/pds.1254
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant prevalence for youths: a multi‐national comparison

Abstract: Cross-national variations should be further explored to understand the factors related to these differences and how prevalence differences relate to effectiveness and safety. Community-based cohorts should be followed to establish outcomes in the usual practice setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
5
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 20 publications
8
79
5
1
Order By: Relevance
“…This finding differs somewhat from those reported from studies conducted in other settings [11,13,22,24,25]. For example, recent Dutch and Italian studies have reported paroxetine to be the most commonly used substance followed by citalopram [11,13].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…This finding differs somewhat from those reported from studies conducted in other settings [11,13,22,24,25]. For example, recent Dutch and Italian studies have reported paroxetine to be the most commonly used substance followed by citalopram [11,13].…”
Section: Discussioncontrasting
confidence: 78%
“…The study population encompassed all Swedish residents aged [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] …”
Section: Study Population and Study Periodmentioning
confidence: 99%
“…The neurobiological mechanisms underlying these effects are unknown. Nevertheless, the antidepressant mechanisms of FLX have been linked to adaptations in postreceptor signaling since chronic, not acute, administration is required for its therapeutic effects Racagni and Popoli, 2008). For example, within the ventral teg-mental area (VTA), a brain region implicated in mood regulation (Nestler and Carlezon, 2006;Chaudhury et al, 2013), brainderived neurotrophic factor (BDNF) and its downstream signaling effectors are compromised in preclinical models of stress , as well as in postmortem VTA samples from MDD patients .…”
Section: Introductionmentioning
confidence: 99%
“…A shift was also detected in the diagnosing of depression in children by a psychiatrist rather than a primary care provider 9 . There are, however, large variations in the prevalence of antidepressant use between various countries 3 and ethnic groups in the United States 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of antidepressants has increased in many Western countries among children, adolescents and young adults, and it has been the subject of numerous studies and a topic of concern [1][2][3][4][5][6] . This increase is mainly due to the introduction of new antidepressants which were anticipated to have fewer side effects, lower toxicity in overdose, and a broader range of treatment indications than older antidepressants.…”
Section: Introductionmentioning
confidence: 99%